Método rápido para detecção de fração antigênica de vermes adultos de Schistosoma mansoni - Mauro Scapin; Miriam Tendler (Revista da Sociedade Brasileira de Medicina Tropical, 1975)
An antigenic fraction of Schistosoma mansoni, obtained from adult worms, has precipttated within 35 minutes with human sera from schistosomotic patients and became visible without staining, using the immunoeletroctroosmophoretic method (I.E.O.F.).